An Efficient and Reliable flooding in MANETs - Jung, Jinman; Cho, Yookun; Kim, Yeongkwun; Yi, Sangho; Park, Hyungbae (Reliable and Autonomous Computational Science, 2010)
Flooding has been used in mobile ad-hoc networks (MANETs) because it is the simplest method for broadcasting messages over an entire network. Several reliable and energy-efficient flooding mechanisms have been developed in recent years. However, an appropriate mechanism which considers dynamic topology changes in MANETs has yet to be developed. Thus, in this paper, we propose an efficient and reliable flooding mechanism. The proposed mechanism uses both FPR and BPR (Forward and Backward Packet Recovery) methods to achieve more robust and reliable flooding. The mechanism enables the receivers to recover missed packets by using the redundant packets in FPR and the request packets for retransmission in BPR. Through analytical modeling, we investigate the impact of redundancy and optimal redundancy in terms of the energy-efficiency in FPR and BPR. In order to maximize the reliability while minimizing network overhead, our mechanism dynamically adjusts the redundancy according to network conditions. Simulation results show that our mechanism provides both increased reliability and energy-efficiency compared to the existing flooding mechanisms.